Anisothermal densification kinetics of the cold sintering process below 150 °C. Issue 17 (22nd April 2020) - Bang, Sun Hwi; Ndayishimiye, Arnaud; Randall, Clive A.
Abstract : Cold sintering is an emerging non-equilibrium process methodology that densifies ceramic powder at significantly reduced temperature and time, and its sintering kinetics can be identified by controlling four densification process variables. Abstract : Cold sintering is an emerging non-equilibrium process methodology that densifies ceramic powders at significantly reduced temperatures. This study proposes a fundamental framework to investigate its densification kinetics. By controlling four densification process variables including the transient chemistry, sintering temperature, uniaxial pressure and dwell time, the anisothermal sintering kinetics of highly densified ZnO is identified and phenomenologically modeled for its relative activation energetics.